Istorijos ir istorijų kūrimas Grahamo Swifto romane Vandens žemė - Rudaitytė, Regina (Literatūra, 2015)
The article focuses on the issue of history as narrative in Graham Swift’s novel Waterland, drawing on Roland Barthes’s theory of the discourse of history as well as on Hayden White’s claim that historical narratives are invented verbal fictions. The postmodernist notion of history denies the fixity of any text, of the past and of any single objective truth about the past. For Swift the creation of history means the reconstruction of the past by means of imagination. Thus in his historiographic metafiction history and imagination are subtly intertwined. History becomes story telling. The opposition between history and story telling is the focus of Swift’s novel. By telling stories its narrator recaptures the lost past, reconstructs his lifestory and by this act constructs history. History as narrative is primarily a personal rather than a factual reality.